Pendidikan Mahad Aly : Menyoal Tradisi Keilmuan Pesantren - Fuaduddin TM (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
Islamic school has a special education system and culture tradition. Today such system and tradition is faced to the challenging and the changing of the area. Pesantren education since the beginning is a tafaqquh fiddin institution in order to make the cadre of the ustadz, which is estimated, happened to the crisis in reproducing the ustadz. Such worry in the next is responded by the leader of Islamic school by establishing of Ma’had Aly. But, in its development, Ma’had Aly faced to some problems and building of since tradition. This article tries to place such Ma’had Aly.